Highlighting the biological potential of the brown seaweed fucus spiralis for skin applications - Freitas, Rafaela (2021)
UID/MAR/04292/2020 PTDC/MAR-BIO/6149/2014 POCI-01-0145-FEDER-016791 SAICTPAC/0019/2015-LISBOA-01-0145-FEDER-016405 PTDC/BIA-OUT/29250/2017 POCI-01-0145-FEDER-029250 Centro-01-0145-FEDER-000018